2007
DOI: 10.1016/j.ssc.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state properties of the one dimensional electron liquid

Abstract: We present a theory of the pair distribution function $g(z)$ and many-body effective electron-electron interaction for one dimensional (1D) electron liquid. Our approach involves the solution of a zero-energy scattering Schr\"odinger equation for $\sqrt{g(z)}$ where we implemented the Fermi hypernetted-chain approximation including the elementary diagrams corrections. We present numerical results for $g(z)$ and the static structure factor $S(k)$ and obtain good agreement with data from diffusion Monte Carlo st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This results in reciprocal lattice points, and the number of q -points needed is which determine the size of the large cell. It has been verified that the implementation reproduces the FHNC/0 result of [ 17 ] in the homogeneous limit. In Fig.…”
Section: The Equations For the Periodic System And Results For A 1d Msupporting
confidence: 64%
See 1 more Smart Citation
“…This results in reciprocal lattice points, and the number of q -points needed is which determine the size of the large cell. It has been verified that the implementation reproduces the FHNC/0 result of [ 17 ] in the homogeneous limit. In Fig.…”
Section: The Equations For the Periodic System And Results For A 1d Msupporting
confidence: 64%
“…The described method is applied to a 1D model system similar to that described by Asgari [ 17 ]. The interaction potential is derived from the electron gas in a homogeneous trap where b characterizes the thickness of the wire.…”
Section: The Equations For the Periodic System And Results For A 1d Mmentioning
confidence: 99%
“…At the same time, we have also observed that the qSTLS ͑as well as STLS͒ theory used by us is not that much successful in 1D as it is for the 3D and 2D electron systems. Interestingly, Asgari 42 has recently found that the Fermi hypernetted-chain approximation, which otherwise accounts quite accurately for the correlation effects in 2D and 3D, does not prove so in a 1D electron system. This clearly suggests that the electron cor- relations are relatively much stronger in 1D as compared to higher dimensional situations.…”
Section: Discussionmentioning
confidence: 99%
“…The harmonic wire has been studied with quantum Monte Carlo (QMC), [38][39][40] variants of the Singwi-Tosi-Land-Sjölander approach, [41][42][43][44] and the Fermi hypernetted-chain approximation. 45 We have studied both the infinitely thin wire and the harmonic wire using QMC. In this article we report QMC calculations of the momentum density (MD), energy, paircorrelation function (PCF), and static structure factor (SSF) of the infinitely thin wire at a variety of densities and system sizes.…”
Section: Introductionmentioning
confidence: 99%